2021
DOI: 10.1021/acs.iecr.1c02730
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism and Kinetics of the Liquid-Phase Oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic Acid

Abstract: 2,5-Furandicarboxylic acid (FDCA), which is currently prepared by catalyzing the oxidation of 5-hydroxymethylfurfural (HMF), is a biobased platform compound with broad market prospects. Herein, a detailed free-radical chain reaction mechanism consisting of both main and side reaction pathways was proposed to describe the liquid-phase air oxidation process of 5hydroxymethylfurfural to 2,5-furandicarboxylic acid over a Co/ Mn/Br catalyst. The higher reactivity of the hydroxymethyl group than the aldehyde group f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…22 Specifically, Avantium has successfully utilized the MC process to produce FDCA at its pilot demonstration factory in Geleen, The Netherlands. 23 and economically viable to oxidize HMF to FDCA using MC, which is essential for an industrial application. The resonance energy of the furan ring (17 kcal/mol) is less than that of the benzene ring (36 kcal/mol), 24 so HMF is more likely to undergo ring-opening and combustion side reactions to generate maleic acid (MA), fumaric acid (FA), and CO x compared to PX.…”
Section: Introductionmentioning
confidence: 99%
“…22 Specifically, Avantium has successfully utilized the MC process to produce FDCA at its pilot demonstration factory in Geleen, The Netherlands. 23 and economically viable to oxidize HMF to FDCA using MC, which is essential for an industrial application. The resonance energy of the furan ring (17 kcal/mol) is less than that of the benzene ring (36 kcal/mol), 24 so HMF is more likely to undergo ring-opening and combustion side reactions to generate maleic acid (MA), fumaric acid (FA), and CO x compared to PX.…”
Section: Introductionmentioning
confidence: 99%
“…Various alternative routes for the production of adipic acid are also discussed with merits and demerits in the literature. 112,108,113–143 Table 1 gives an idea about the various types of catalyst used and its activity for the cyclohexane oxidation.…”
Section: Applications Of the Selective Oxidationsmentioning
confidence: 99%
“…221 Scheme 2 Catalytic mechanism scheme for the free-radical oxidation of 5-HMF to FDCA over Co/Mn/Br catalyst. 118 Catalysis Science & Technology Mini review catalyst was found selective for the oxidation of hydrocarbons using TNHP and O 2 /sacrificial aldehyde as oxidants. 115 In 2007, Lignier et al reported free-radical chain mechanism of gold-catalyzed hydrocarbon oxidation in liquid phase.…”
Section: Liquid-phase Oxidation Via Free Radical Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Among biobased chemicals, 5-hydroxymethylfurfural (HMF) has gained the most attention because it is in the top “10 + 4” list . Moreover, HMF-derived chemicals such as 2,5-dimethylfuran, 2,5-furan dicarboxylic acid, and levulinic acid are widely used in different fields. In previous studies, using fructose as a feedstock could provide the most promising HMF yield, , but high fructose price makes this route uneconomical.…”
Section: Introductionmentioning
confidence: 99%